IMPLEMENTASI KEBIJAKAN POLA TATA KELOLA BADAN LAYANAN UMUM DAERAH (BLUD) DI RSUD BANGKINANG (STUDI KASUS PADA PELAYANAN RAWAT INAP TAHUN 2018) - Haris, Ikhsan; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Kampar Regent Regulation number 10 of 2015 concerning "The Pattern of Governance of the Regional Public Service Agency of the Bangkinang Regional General Hospital", this policy contains the BLUD in Bangkinang Hospital along with technical/rules in carrying out their service duties. The essence or purpose of this BLUD requires hospitals to be better able to create efficiency in improving the quality of better services. set standard. There are complaints of inpatients against slow medical treatment and it is known that inpatient Human Resources (HR) are still weak, and from some of the employees on duty in the inpatient care there are even those who do not fully understand the rules/policies.The purpose of this study is to describe the implementation of the Regional Public Service Agency Governance Pattern (BLUD) policy at the Bangkinang Regional General Hospital on the implementation of services in inpatient service units in 2018. This study uses the theory of Policy Implementation by Edward III. With descriptive method, this type of research is qualitative. The types of research data are primary data and secondary data. Data collection techniques with documentation and interviews. Qualitative descriptive data analysis techniques.The results of the study indicate that the implementation of these policies in 2018 is generally in the not good enough category. The aspects that support the results of this research are; 1). The communication aspect has not been implemented optimally, 2). The resource aspect is quite effective, 3). Aspects of disposition, showing a fairly good response, and 4). Aspects of the bureaucratic structure with the dimensions of standard operations and procedures (SOP) of BLUDs have been well guided, only need to increase the consistency of employees to stricter rules. It is known that the obstacles faced in the inpatient service unit at that time were; 1). there are several employees who are hospitalized who do not fully understand the contents of the policy, 2). employee indiscipline, 3). inpatient installations are still a little short of staff/medical personnel, 4). One of the delayed revenues of the Bangkinang Hospital caused the hospital to be slightly short of funds, so that it had an impact on the employees and also the quality of the services at the hospital.Keyword: Policy Implementation, Service, BLUD.